Catalytic Conversion of Ethanol and Isopropanol on γ-Irradiated CoO/AlO Solids - M.M. Doheim; H.A. El-Boohy; G.A. El-Shobaky (Adsorption Science & Technology)
The catalytic conversion of ethanol and isopropanol was conducted over Co 3 O 4 /Al 2 O 3 solids (19.3 wt% Co 3 O 4 ) precalcined at 400°C and subjected to different doses of γ-radiation. The reaction was studied at different temperatures in the range 250–400°C and monitored using nitrogen as a carrier gas flowing at a rate of 18 cm 3 /min. The γ-ray doses employed were 0.2, 0.4, 0.8 and 1.6 MGy, respectively. The results obtained indicated that γ-irradiation effected a progressive decrease in the catalytic activity of the solids towards alcohol conversion, reaching a minimum value after 0.8 MGy irradiation. The irradiation process also effected a measurable decrease in the dehydration selectivity towards the alcohols investigated and an increase in their dehydrogenation selectivity. These results were discussed in terms of an effective decrease in the concentration of sites exhibiting Brönsted acidity brought about by γ-irradiation, which also generated a small decrease in the particle size of the Co 3 O 4 crystallites and a measurable increase in the specific surface areas of the solids investigated.